Effects of maize straw and corncob return on the soil quality and on the soil microbial structures and functions - Zhong, Yu; Li, Ruoyu; E, Jiayi; Chi, Hai; Cao, Ning; Bai, Zhongyi; Du, Xinglin; Wang, Le (Frontiers in Microbiology, 2025)
Straw return is an effective agricultural strategy for incorporating organic carbon into soil organic matter pools through microbial decomposition. This process modifies soil physicochemical properties, thereby altering microbial habitats and resource availability, which can influence the structure and function of soil microbial communities. However, the changes of soil physicochemical properties and microbial communities under different straw incorporation forms remain poorly understood. And how these straw return materials alter soil physicochemical properties and microbial communities within a single cycle. In this study, we conducted straw returning experiments in a maize-producing region of Jilin Province, China, comparing the impact of two distinct maize-derived residues (crushed maize straw and crushed corncob) on soil quality and microbial communities. Our results demonstrated that corncob return more effectively improved key soil physicochemical properties compared to maize straw return. While neither residue significantly alters microbial alpha diversity, both induced shifts in beta diversity. We identified distinct correlations between dominant microbial taxa and key soil physicochemical parameters. Furthermore, KEGG and GO analyses revealed that both of the residues altered microbial functional hierarchies, with corncob return inducing more pronounced changes than maize straw return. These findings provide a mechanistic basis for optimizing straw management strategies to enhance microbial-mediated soil fertility.